From front-end to back-end and everything in-between: work practice in game development - Koleva, Boriana; Tolmie, Peter; Brundell, Patrick; Benford, Steve; Rennick-Egglestone, Stefan (ACM, 2015)
This paper addresses a paucity in the literature of studies of actual game development. It presents the initial findings from a questionnaire addressed to game development companies together with an ethnographic case study that drills into how resources are actually used and how the workflow and coordination are actually accomplished. It finds a number of challenges that can be seen to confront the development of new game authoring tools, centred around the intensely co-present character of design-related interaction and collaboration in this domain. These findings are used to articulate a range of potential requirements.